Dr. Dog - Cole, Babette (New York : Distributed by Random House, 1997)
The Gumboyle family's dog is also a doctor who cares for their illnesses and gives them tips on health care and hygiene.
Booklist.
Publisher's Weekly.
School Library Journal.
2.2.
2.2
K-3
Keywords: Dogs -- Juvenile fiction; Cleanliness -- Fiction; Dogs -- Fiction; Grooming -- Fiction; Health -- Fiction; Physicians -- Fiction; Cleanliness -- Fiction; Dogs -- Fiction; Health -- Fiction; Personal grooming -- Fiction; Physicians -- Fiction